Motivations and Future Intentions in Sport Event Volunteering: A Systematic Review - Salvador Angosto (MDPI AG, 2021)
Understanding the future intentions of individuals who are part of a sport organization is a critical step for the success and the accomplishment of the goals of such organizations, particularly for sporting events that highly depend on the work of volunteers. Therefore, it is important to determine which factors motivate an individual to volunteer, as well as the intentions volunteers have to continue volunteering for sporting events or other similar organizations. This study conducted a systematic review of literature on studies that have examined the motivation and future intentions of volunteering in sporting events. The PRISMA methodology was used to develop this review. It included 30 studies from 2007 to 2020, and all the studies examined these two constructs using different types of quantitative methodologies. Moreover, most of these studies were conducted by scholars in the United States and Australia, and the VMS-ISE was the most used instrument for collecting data. Many of the studies did not include a theoretical framework relating motivation and future intentions to other constructs. The results of this systematic review provide new insights regarding the state of studies that have examined future intentions related to volunteering in sporting events, particularly regarding how to plan future investigations of volunteers’ motivation and future intention in the context of sporting events.